Reimagining how to understand learning game experiences: a qualitative and exploratory case study - Håvard Almås; Felix Pinkow; Fay Giæver (Smart Learning Environments, 2023)
Abstract While the use of games for learning in higher education is well established, existing research provides limited understanding of individual experiences that shape engagement and learning in collaborative learning games. Insights into players’ individual experiences can, however, contribute to a more nuanced utilization of learning games and to better understand differences in individual learning outcomes. Therefore, this study seeks to explore how learning is experienced by players in a collaborative learning game. To achieve this, the study investigates the incentive and interaction dimensions of learning and the role of engagement and motivation for learning in an online collaborative board game using an exploratory qualitative case study approach. The study draws on diverse data comprising several sources, including in-depth interviews, observation of participants during a learning game, written free-form feedback, and a survey regarding the play experience. Results accentuate the role of individual and contextual differences, especially pertaining to prior knowledge and applying knowledge in realistic settings, perception of novelty related to game learning, and support from instructors and group members. Findings are further contextualized by positioning them into theoretical foundations related to transactive memory systems and collaborative engagement. Suggestions are made for collaborative learning game practitioners to strive for intragroup acquaintance and establishing purpose and use before play, and for instructors to be trained to dynamically adapt the type and amount of support provided based on player needs.